Society, Technology, and Child Protection: Synergy in Monitoring Former Perpetrators of Sexual Offenses - Asri Yustia, Rd. Dewi; Faris Fachrizal Jodi; Firdaus Arifin (Jurnal IUS Kajian Hukum dan Keadilan, 2026)
Children are important national asset who require special protection from all forms of violence, including sexual crimes. Although Indonesia has established legal framework at both national and international levels, sexual violence against children remains a persistent problem. The imposition of severe criminal sanctions, including chemical castration, has not sufficiently addressed the problem and produced an optimal deterrent effect. Consequently, child protection continues to face various challenges, particularly in relation to post-sentencing supervision of offenders, low public awareness, and limited access to victim assistance services. The research questions of this study are: how effective is the legal protection for child victims of sexual violence, and what constitutes an effective supervisory model for offenders after serving their sentences in order to prevent recidivism? This study employs legal research with a socio-legal approach, combining normative juridical analysis with perspectives from information technology and social sciences. The findings indicate the need to strengthen post-sentencing supervision through the development of a Three-Pillar Supervision Model that integrates legal, technological, and societal dimensions. This model includes the optimization of technologies such as GPS tracking and public databases, the strengthening of regulatory frameworks, and the societal involvement in early detection mechanisms. The implementation of this model is expected to reduce the risk of recidivism and strengthen sustainable protection for children. Accordingly, reform of the child protection system must be carried out in a collaborative, preventive, and sustainable manner to ensure justice and security for future generations.